2019
DOI: 10.1016/j.neuroimage.2018.10.019
|View full text |Cite
|
Sign up to set email alerts
|

First-year development of modules and hubs in infant brain functional networks

Abstract: The human brain develops rapidly in the first postnatal year, in which rewired functional brain networks could shape later behavioral and cognitive performance. Resting-state functional magnetic resonances imaging (rs-fMRI) and complex network analysis have been widely used for characterizing the developmental brain functional connectome. Yet, such studies focusing on the first year of postnatal life are still very limited. Leveraging normally developing longitudinal infant rs-fMRI scans from neonate to one ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 75 publications
12
71
0
Order By: Relevance
“…Also, symptom severity (reported using HAM-D) was positively correlated with modularity (Ye et al, 2015). As modularity has been shown to gradually increase in the first year of life (Wen et al, 2018), it might be that alterations in global modularity do not exist in the neonatal brain but might develop over time. Also, mothers in our cohort showed only mild-depressive symptoms (see Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, symptom severity (reported using HAM-D) was positively correlated with modularity (Ye et al, 2015). As modularity has been shown to gradually increase in the first year of life (Wen et al, 2018), it might be that alterations in global modularity do not exist in the neonatal brain but might develop over time. Also, mothers in our cohort showed only mild-depressive symptoms (see Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…A multivariate GLM analysis corrected for sex, age at the MRI, and PES revealed group differences between the depressed-only and control groups for the amygdala, and between SSRI and depressed-only for the right frontal orbital and left Heschl gyrus corrected for multiple comparisons, Bonferroni (also see Table S4a,b). As modularity has been shown to gradually increase in the first year of life (Wen et al, 2018), it might be that alterations in global modularity do not exist in the neonatal brain but might develop over time. Dark green circles represent provincial hubs, and red circles represent connector hubs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different functional sub-networks are developed with diverse developmental trajectories, with primary systems mature earlier than high-order function-related systems Gao et al, 2015). From the local level, our recent findings suggest that more association regions gradually emerge as connector hubs facilitating information exchange and integration among functional sub-networks, while many primary regions become less centralized (Gao et al, 2011;Wen et al, 2019). Although providing valuable insights, these studies all investigate FC from a "static" point of view, ignoring its essential "temporal dynamics".…”
Section: Introductionmentioning
confidence: 96%
“…Based on this method, existing studies have revealed the brain functional network development at multiple levels, including global (i.e., whole brain) (Gao et al, 2011;Wen et al, 2019), mesoscale (i.e., functional sub-networks) (Gao and Lin, 2012b;Gao et al, 2014;Gao et al, 2015;) and local levels (i.e., brain regions) (Wen et al, 2019). Generally, the brain network is globally reconfigured to be more efficiently balanced between local and global information communications from neonates to two years of age (Gao et al, 2011;Wen et al, 2019). Different functional sub-networks are developed with diverse developmental trajectories, with primary systems mature earlier than high-order function-related systems Gao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%